Answer:
7
Step-by-step explanation:
For this case, what we must do is fill squares in all the expressions until we find the correct result.
We have then:
x2 + y2 − 4x + 12y − 20 = 0 x2 + y2 − 4x + 12y = 20
x2 − 4x + y2 + 12y = 20
x2 − 4x + (12/2)^2 + y2 + 12y + (-4/2)^2 = 20 + (12/2)^2 + (-4/2)^2
x2 − 4x + (6)^2 + y2 + 12y + (-2)^2 = 20 + (6)^2 + (-2)^2
x2 − 4x + 36 + y2 + 12y + 4 = 20 + 36 + 4
(x − 2)2 + (y + 6)2 = 60
3x2 + 3y2 + 12x + 18y − 15 = 0
x2 + y2 + 4x + 6y − 5 = 0
x2 + y2 + 4x + 6y = 5
x2 + 4x + (4/2)^2 + y2 + 6y + (6/2)^2 = 5 + (4/2)^2 + (6/2)^2
x2 + 4x + (2)^2 + y2 + 6y + (3)^2 = 5 + (2)^2 + (3)^2
x2 + 4x + 4 + y2 + 6y + 9 = 5 + 4 + 9
(x + 2)2 + (y + 3)2 = 18
2x2 + 2y2 − 24x − 16y − 8 = 0
x2 + y2 − 12x − 8y − 4 = 0
x2 + y2 − 12x − 8y = 4
x2 − 12x + (-12/2)^2 + y2 − 8y + (-8/2)^2 = 4 + (-12/2)^2 + (-8/2)^2
x2 − 12x + (-6)^2 + y2 − 8y + (-4)^2 = 4 + (-6)^2 + (-4)^2
x2 − 12x + 36 + y2 − 8y + 16 = 4 + 36 + 16
(x − 6)2 + (y − 4)2 = 56
x2 + y2 + 2x − 12y − 9 = 0
x2 + y2 + 2x - 12y = 9
x2 + 2x + y2 - 12y = 9
x2 + 2x + (2/2)^2 + y2 - 12y + (-12/2)^2 = 9 + (2/2)^2 + (-12/2)^2
x2 + 2x + (1)^2 + y2 - 12y + (-6)^2 = 9 + (1)^2 + (-6)^2
x2 + 2x + 1 + y2 - 12y + 36 = 9 + 1 + 36
(x + 1)2 + (y − 6)2 = 46
Answer:
Option A is correct.
10 square centimeters.
Step-by-step explanation:
Complete Question
The complete Question is attached in the first attached image.
Lydia cut out her initial from a piece of construction paper. How many square centimeters of construction paper are used to make Lydia's initial?
A) 10 square centimeters
B) 11 square centimeters
C) 15 square centimeters
D) 22 square centimeters
Solution
From the second attached image, it is evident that we can split the L-shaped figure into two rectangles of dimensions (3 cm by 1 cm) and (7 cm by 1 cm)
The total area of the figure is thus
(3 × 1) + (7 × 1) = 10 cm²
Hope this Helps!!!
Answer:
The probability is 2/5.
Step-by-step explanation:
4/5 is the probability of not getting a 5
1/2 is the probability of flipping heads
4/5x1/2 = 4/10 = 2/5
From the steps shown in the table given, we can conclude that: D. in solving the equation, the subtraction property of equality was not applied.
<h3>What is the Subtraction Property of Equality?</h3>
If a + b = c, to apply the subtraction property of equality so that b is moved to the other side of the equation, we would have:
a + b - b = c - b
a = c - b
Thus, from the table given, the none of the steps showed that the subtraction property of equality was applied in solving the equation, so, the answer is: D.
Learn more about the subtraction property of equality on:
brainly.com/question/1601404
#SPJ1